Evaluation of cool roof and vegetations in mitigating urban heat island in a tropical city, Singapore - Li, Xian-Xiang; Norford, Leslie K. (Urban climate, 2016)
•A high-resolution numerical simulation of UHI in a tropical city is performed.•Cool roof and vegetation both can reduce air temperature, but at different times.•Green vegetation is preferable in reducing the nocturnal UHI in a tropical city. A numerical study with a weather research and forecasting (WRF) model at 300-m resolution shows that Singapore’s canopy-layer UHI intensity has a strong diurnal cycle, peaking in early morning and keeping almost constant during late night and early morning. The modeled ensemble peak UHI intensity is 2.2°C and it can reach 2.4°C during early morning in the intensive industrial region in west Singapore. Numerical sensitivity tests are carried out to evaluate the mitigation effect of the cool roof and green vegetations at the city scale. The results reveal that the city-scale deployment of cool roofs can greatly reduce the near-surface air temperature and surface skin temperature during the daytime (especially at noon), but has little effect during nighttime. Green vegetation deployment, however, can reduce the near-surface air temperature by more than 1°C during nighttime when the UHI intensity is high. This reduction can reach 2°C at 02:00LT in western Singapore. The detailed analysis shows that the higher latent heat flux and lower heat storage during daytime in green vegetation deployment are the key factors that contribute to the lower sensible heat flux, and hence lower near-surface air temperature. Moreover, the green vegetation will improve human’s physiological thermal comfort during early morning. It is therefore suggested that, under the specific meteorological conditions, the green vegetation is preferable in terms of mitigating the (nocturnal) UHI intensity in Singapore, albeit with some uncertainties and caveats to be considered in practice.